Systemic lupus erythematosus activity and beta two microglobulin levels - Skare, Thelma Larocca; Ferri, Kellen; Santos, Marcela Aimone (São Paulo Medical Journal, 2014)
CONTEXT AND OBJECTIVE: Systemic lupus erythematosus (SLE) is an autoimmune disease with a cyclical clinical course. Evaluation of the clinical activity of this disease is important for choosing the correct treatment. The objective of this study was to analyze the value of beta-2 microglobulin (β2M) serum levels in determining SLE clinical activity. DESIGN AND SETTING: Cross-sectional analytical study conducted at the rheumatology outpatient clinic of a private university hospital. METHODS: 129 SLE patients were studied regarding disease activity using SLEDAI (SLE Disease Activity Index) and cumulative damage using SLICC ACR (SLE International Collaborating Clinics/American College of Rheumatology Damage Index for SLE). At the same time, the β2M serum level, ESR (erythrocyte sedimentation rate), anti-dsDNA (anti-double-stranded DNA) and C3 and C4 complement fractions were determined. RESULTS: β2M levels correlated positively with SLEDAI (P = 0.02) and ESR (P = 0.0009) and negatively with C3 (P = 0.007). Patients who were positive for anti-dsDNA had higher β2M serum levels (P = 0.009). CONCLUSION: β2M levels are elevated in SLE patients with active disease.